TO PETITION FP93-1 - SMITH,PF (Tufts Archival Research Center, 2007)
Letter from Peter Smith, President of Fire Fighters Association of New Jersey , to Consumer Products Safety Commission expressing support for federal upholstered furniture flammability standards as tough as those in California. Discusses responsibility and ability of furniture industry to make safer furniture, as well as furniture-related fire deaths and safety issues. Recommends a uniform nationwide standard instead of individual state standards, while expressing difficulties encountered in raising standards in New Jersey.